CONCEPTUAL BASE OF THE SITUATION MANAGEMENT BY WORK BUILDING PROJECT - N. M. Gasanova; Sh. T. Ismailova (Вестник Дагестанского государственного технического университета: Технические науки)
They are offered conceptual bases of the shaping the situation management by process to realization of the working the building project. The main indicators of the structured description of works of the construction project are specified. The designed methods of work execution management on result and time to their realization.